PENGARUH PERENDAMAN DAN LETAK BENIH PADA BAGIAN TONGKOL TERHADAP VIABILITAS BENIH JAGUNG (Zea mays L.) - Mulyono, Mulyono; Rahmi, Faidha; Putra, Rezkan (Cangkok, 2024)
This research aims to determine the influence of corn seed viability and to determine the influence of interactions between these two factors. This research was carried out in the laboratory of the Faculty of Agriculture, Gajah Putih University, Takengon at an altitude of 1237 above sea level. The parameters observed consisted of Growth Potential at 5 and 10 days after sowing, Germination Power at 5 and 10 days after sowing, Wet Stove Weight at 5 and 10 days after sowing, and Dry Stove Weight at 5 and 10 days after sowing. seedling. The results of the research showed that the soaking treatment and the location of the seeds on the cob had a significant effect on growth potential at the age of 5 and 10 days after sowing. There was no real interaction between Soaking and Seed Location on the Cob in each observation.